2006
DOI: 10.1029/2006gl026355
|View full text |Cite
|
Sign up to set email alerts
|

Thermocline flux exchange during the Pinatubo event

Abstract: [1] We analyze the temperature anomaly of the Pinatubo eruption using an exact mathematical solution of a standard energy balance model that includes coupling between the mixed layer and the thermocline. Our solution yields a short response time t = 4.4 months and a small climate sensitivity l = 0.22 C/(W/m 2 ), implying short-term negative feedback. Also, our analysis determines a value of the effective eddy diffusion constant k = 2 Â 10 À6 m 2 /s that is much smaller than that assumed in many climate models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…We resist the temptation to assess climate feedback immediately after the four major eruptions since 1900 because our framework is based upon stratospherically adjusted RF, and relating the ERBE measurements (top of atmosphere) to the tropopause is beyond the scope of this study. If the true influence of Pinatubo on global cooling is as small as suggested by our lower limits, and there was indeed a strong, global, negative RF anomaly at the tropopause, then perhaps there was a negative feedback following the eruption of Pinatubo, as suggested by Douglass and Knox (2005) and Douglass et al (2006). Stenchikov et al (2009) state; "In this study, Pinatubo aerosols globally decrease the incoming net radiative flux at the top of the atmosphere by about 3 W m −2 at maximum that is consistent with most of the IPCC-AR4 models .…”
Section: T Canty Et Al: a Critical Evaluation Of Volcanic Coolingmentioning
confidence: 86%
See 1 more Smart Citation
“…We resist the temptation to assess climate feedback immediately after the four major eruptions since 1900 because our framework is based upon stratospherically adjusted RF, and relating the ERBE measurements (top of atmosphere) to the tropopause is beyond the scope of this study. If the true influence of Pinatubo on global cooling is as small as suggested by our lower limits, and there was indeed a strong, global, negative RF anomaly at the tropopause, then perhaps there was a negative feedback following the eruption of Pinatubo, as suggested by Douglass and Knox (2005) and Douglass et al (2006). Stenchikov et al (2009) state; "In this study, Pinatubo aerosols globally decrease the incoming net radiative flux at the top of the atmosphere by about 3 W m −2 at maximum that is consistent with most of the IPCC-AR4 models .…”
Section: T Canty Et Al: a Critical Evaluation Of Volcanic Coolingmentioning
confidence: 86%
“…Douglass and Knox (2005) conducted a regression analysis of MSU lower tropospheric temperature measurements and concluded the atmosphere exhibited a negative feedback following the eruption of Pinatubo. This paper has been discussed in a series of published comments and replies following initial publication, concluding with another paper, Douglass et al (2006), that reinforces their notion of a negative feedback within the climate system in the short time period following the Pinatubo eruption. Our estimates of climate feedback, given above, represent a best fit to the entire 111 yr temperature record, without direct focus on the time period immediately following major eruptions.…”
Section: T Canty Et Al: a Critical Evaluation Of Volcanic Coolingmentioning
confidence: 93%
“…This effect should, if correct, provide a powerful negative feedback. As mentioned earlier, ocean delay is itself proportional to climate sensitivity, and the work of Lindzen and Giannitsis (1998) and Douglass et al, (2006) strongly suggested that the observed delay time is too short to allow large sensitivities.…”
Section: "The Size Of the Recently Observed Global Warming Over A Fementioning
confidence: 99%
“…Many estimates based on those methods have therefore been criticized; we generally have low confidence in relying on them in this assessment, but provide further references to studies and critical comments here for completeness 7,24,56,93,225,231,259,269, . Similarly, the response to volcanic eruptions provides a test for models 302 but in our view the implications for ECS are unclear since the timescale and type of forcing is very different, the feedbacks arising are different, and the response is difficult to separate from El Niño variability 185,[303][304][305][306][307][308][309][310][311] . It has also been attempted to estimate TCR from the observed temperature response to the sunspot cycle 312 .…”
Section: Constraints From the Observed Transient Warmingmentioning
confidence: 99%